At frigøre (sig fra) mors begær - Om Lars von Triers Antichrist - Rösing, Lilian Munk (Slagmark - Tidsskrift for idéhistorie, 2018)
Lars von Trier’s chef-d’oeuvre Antichrist (2009) was immediately criticized, especially by pronounced feminist reviewers, for being misogynistic and excessively violent. The article discusses these criticisms and argues that they bound in a failure to appreciate the aesthetic dimensions of the film. Instead, it is claimed that Antichrist can essentially be read as a dream that unfolds the primal scene (the child observing his parents having sex); in the prologue its angelic, liberating side, and throughout the rest of the movie its brutal and traumatic side. As such, Antichrist is an attempt at traversing the impossible relation between the sexes much more than it is a portrait of any particular traits of men or women.